2009
DOI: 10.1073/pnas.0809979106
|View full text |Cite|
|
Sign up to set email alerts
|

The substrate-binding protein imposes directionality on an electrochemical sodium gradient-driven TRAP transporter

Abstract: Substrate-binding protein-dependent secondary transporters are widespread in prokaryotes and are represented most frequently by members of the tripartite ATP-independent periplasmic (TRAP) transporter family. Here, we report the membrane reconstitution of a TRAP transporter, the sialic acid-specific SiaPQM system from Haemophilus influenzae , and elucidate its mechanism of energy coupling. Uptake of sialic acid via membrane-reconstituted SiaQM depends on the presence of the sialic acid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
134
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 103 publications
(149 citation statements)
references
References 30 publications
15
134
0
Order By: Relevance
“…3) led to a K d value, which is close to previously determined values using isothermal titration calorimetry (ITC) or Trp fluorescence quenching (5,6,23). This suggests that the PELDOR data can be quantitatively analyzed and, judged by the error calculated from the linear combination fitting of VcSiaP Q54R1/L173R1 time traces, it appears that as little as 3% of the closed conformation can be detected (Table S2).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…3) led to a K d value, which is close to previously determined values using isothermal titration calorimetry (ITC) or Trp fluorescence quenching (5,6,23). This suggests that the PELDOR data can be quantitatively analyzed and, judged by the error calculated from the linear combination fitting of VcSiaP Q54R1/L173R1 time traces, it appears that as little as 3% of the closed conformation can be detected (Table S2).…”
Section: Discussionsupporting
confidence: 85%
“…The Q-and M domains are either fused into one protein or expressed as separate proteins that form a tight complex (4). As indicated by their name, TRAP transporters are independent of ATP hydrolysis and some representatives have been shown to rely on a Na þ gradient and membrane potential to power the transport mechanism (5,6). This is considered a reason why TRAPs are especially widespread in marine microorganisms (7).…”
Section: Introductionmentioning
confidence: 99%
“…The key difference between ATPbinding cassette and TRAP transporters is that although ATPbinding cassette transporters are primary transporters, TRAP transporters are secondary transporters that use electrochemical gradients across the membrane to energize uptake (3,4). Much progress has been made recently in the understanding of the structure and function of SBPs from TRAP transporters (5-11), but our knowledge of the membrane components is much poorer.…”
mentioning
confidence: 99%
“…This genomic element is found only in pathogenic strains of V. cholerae and its presence correlates with the ability of vibrio species to utilize sialic acid (Almagro-Moreno & Boyd, 2009). As well as containing the catabolic genes (the nan cluster), VPI-2 also contains genes for a tripartite ATP-independent periplasmic (TRAP) transporter, siaPQM (VC1777-9), orthologous to the well-characterized sialic acid TRAP transporter from Haemophilus influenzae (Severi et al, 2005;Allen et al, 2005;Müller et al, 2006;Johnston et al, 2008;Mulligan et al, 2009). Indeed we have demonstrated that SiaP from V. cholerae (VC1779) is a high-affinity sialicacid-binding protein (Mulligan et al, 2009) and have functionally reconstituted the whole transporter which is active for sialic acid uptake into proteoliposomes (unpublished data).…”
mentioning
confidence: 99%